Analisis Penerapan K3 di Pabrik Perkebunan Sawit: Literatur Review - Nur Elviyani Sinaga; Tri Rahma Sintia; Rizka Aulia; Sri Hajijah Purba (Jurnal Anestesi, 2024)
. Implementing a culture of safety or safe work in oil palm plantations is very difficult for the workforce, especially those with low education. The palm oil industry faces many risks, including heat exposure, heavy workloads, exposure to hazardous chemicals, fires, and accidents due to heavy equipment. OHS is still seen as a cost and not an investment to prevent work accidents in companies or industries. The purpose of this study was to summarize the journal and find important information about the implementation of OSH in palm oil mills. In writing this journal, a literature review approach was used. The journals used in this study came from journals accessed through Google Schoolar. The results showed that there are several factors that cause To conduct this research, the activities needed to identify risks in the work process, such as fire, fall risk, heat exposure, chemical exposure, and occupational accidents. To conduct this research, the necessary activities to identify risks in the work process at the.